Efeito inseticida de vicilinas isoladas de sementes de erythrina velutina em condições de semi-campo para moscas das frutas (ceratitis capitata) - Macedo, Cleysyvan de Sousa (2010)
Chitin-binding vicilins from legume seeds (Erythrina velutina. Canavalia ensiformes and Phaseolus vulgares) were isolated by ammonium sulfate followed by affinity chromatography on a chitin column. Effect of these vicilins on female adults of Ceratitis capitata was examined by bioassay and in a semi-field assay model. Mechanism of action of the vicilins was determined by in vivo digestibility and chitin affinity. Among the tested vicilins, E. velutina when added to diet caused strong effect on mortality at 10% dose. This insecticidal property was tested in a semi-field assay which showed the same effect observed in laboratory conditions, where doses of 10% and 15% were lethal to female adults of C. capitata. These deleterious effects were not only associated to the binding to chitin structures present in peritrophic membrane, but principally to its low digestibility in the C. capitata digestive tract. This fact was confirmed because chiting binding proteins as WGA and the other tested vicilins were not toxic to female adults of C. capitata due susceptibility of these proteins to digestive enzymes of the insects. By other side EvV was more resistant to digestive enzymes, causing deleterious effects on female adults of C. capitata. These results showed that EvV may be part of the pest management programs or an alternative in plant improvement program in the population control of this fruticulture pest